Expressão heteróloga e localização subcelular de seis proteínas possivelmente envolvidas com a Síndrome de Down - Justino, Daniela Morilha Néo (2004)
Down syndrome (DS) is the most common congenital disease occurring in approximately 1 out of 700 live births. In addition to the full HC21 trisomy, rare individuals with clinically recognized DS have only a partial trisomy, carrying a region common to all patients dubbed as Down Syndrome Critical Region (DSCR). Several genes contained in this portion of the HC21 are probably related to the DS phenotypes. In an attempt to characterize some of the DSCR genes, heterologous expression and subcellular localization analyses were performed for the genes DCRB (DSCR4), c21orf45, c21orf59, c21orf83-2, c21orf 95 and c21orf101. Analyses of the recombinant proteins produced in Escherichia coli showed that most of them remained in the insoluble fraction. DCRB was expressed as a soluble protein in E. coli Rosetta (DE3), purified and subjected to assays for secondary structure analyses. Also, deletion and site directed mutagenesis as well as the production of polyclonal antisera against DCRB were performed. Subcellular localization analyses revealed that the proteins DCRB, c21orf45, c21orf59 and c21orf83-2 were distributed in the cytoplasm of mammalian cells and that c21orf95 and c21orf101 resided in the nucleus. Considering the lack of information concerning these proteins encoded in the DSCR our results allowed a insight into some of the proteins provably involved in Down syndrome.